The nutritional management of people living with amyotrophic lateral sclerosis: A national survey of dietitians. Issue 6 (24th April 2021) - White, Sean; Zarotti, Nicolò; Beever, Daniel; Bradburn, Mike; Norman, Paul; Coates, Elizabeth; Stavroulakis, Theocharis; White, David; McGeachan, Alexander; Williams, Isobel; Hackney, Gemma; Halliday, Vanessa; et al.
Abstract: Background: People living with amyotrophic lateral sclerosis (ALS) face many challenges with respect to taking adequate nutrition. Growing evidence links weight loss with negative prognostic outcomes. We aimed to explore the practice of dietitians in the UK with regard to the nutritional management of ALS. Methods: A national online survey was disseminated via professional groups, social media and newsletters to UK healthcare professionals between September and November 2018. The survey examined the nutritional management of ALS. Dietitian responses are reported in the present study. Results: In total, 130 dietitians responded to the survey. Two‐thirds reported that ALS comprised less than 20% of their total patient caseload. Forty‐two percent reported that nutritional screening took place in their organisation. One‐half of dietitians reported that patients were referred for dietetic assessment at 'about the right time', although 44% reported referrals were made too late. The majority (83%) of dietitians used resting energy expenditure predictive equations not validated in ALS. When setting weight goals, dietitians reported most frequently recommending weight maintenance if the patient's body mass index was 18.5–25 kg m −2 (72%), 25–30 kg m −2 (98%), and > 30 kg m −2 (79%). In addition, 43% reported that people with ALS were not weighed sufficiently frequently. Conclusions: Although the importance of early nutritional assessment is recognised, the timeliness of dietetic input and on‐going monitoring of nutritional status in ALS care might not currently be ideal. Dietitians report using energy requirement predictive equations and setting weight goals that may not promote positive outcomes. Further research is required to understand the optimal nutritional management of ALS. Abstract : The responses by UK dietitians ( N = 130) to a cross‐sectional survey exploring the nutritional management of people living with amyotrophic lateral sclerosis (ALS) (also known as motor neurone disease) are reported . The findings include that dietitians report: people with ALS are referred late for specialist dietetic assessment; the use of predictive calorie requirement equations that are not validated for people with ALS; and the setting of weight goals that are not consistent with the current ALS evidence base. Further research is required to study the optimal nutritional management of people with ALS.